Przeskalowanie wyobraźni: maszyna językowa i poezja - Winiecka, Elżbieta (Przestrzenie Teorii, 2024)
The article is focused on the peculiarities and functions of metaphors in the poetry of Radosław Jurczak, and more broadly in the work of the youngest poets, for whom life in the world of digital media and the perspective of the development of artificial intelligence is an important part of their formative experience. She uses the terms introduced by Mark Fisher for this purpose: weird and eerie. The authoress compares poetic tricks appearing in Jurczak’s poems with the concept of poetic language of the first avant-garde. She points out the changes occurring in the poetics and aesthetics of the works, and also focuses on figures relating to the technological sphere of modernity. She polemically addresses the view of Jerzy Jarzębski, who considers the phrase “artificial intelligence” to be a fashionable and harmful oxymoron that defines the pragmatic, reductionist worldview of its users. The authoress argues that the incorporation into the language of poetry of terms that have in everyday language the status of catachreses and over-lexicalized metaphors, allows to recover their creative potential and ambiguity. She considers the characteristic feature of the new poetic imagination to be its scaling, which also requires readers to take a new approach to the language of the new poetry.